Gross renal morphology of the numbat (Myrmecobius fasciatus) (Marsupialia : Myrmecobiidae) - Cooper, Christine; Withers, P. (2010)
There is a strong correlation between the structure of the mammalian kidney and its urinary concentrating ability. We examine here the kidney of an endangered termitivorous marsupial (Myrmecobius fasciatus) and use the measured kidney morphometrics to calculate maximal urinary concentration. The relative medullary area (1.34) of the kidney of M. fasciatus is typical of other dasyuromorph marsupials, as is its predicted maximal urinary concentration of 3617 mOsm kg–1 H2O, despite its historically semiarid/arid distribution. The termitivorous diet of M. fasciatus presumably provides it with sufficient water to limit selection for a high urinary concentrating capacity.